Investigation of the elastic scattering of 3 Hе from 9 Bе in within the framework the optical and folding models - Мендибаев , К.О.; Джансейтов, Д.М.; Кутербеков, К.А.; Жолдыбаев, Т.К.; Исатаев, Т.Г.; Азнабаев, Д.Т.; Валиолда, Д.С.; Кабышев, А.М.; Лукьянов, С.М.; Пенионжкевич, Ю.Э.; Уразбеков, Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Processes of elastic scattering of 3 Hе from 9 Bе nuclei at energies30, 40 and 47 MeV were studied in this paper. The experimental angular distributions of the elastic scattering of 3 Hе on 9 Bе nuclei were measured on the extracted beams of the cyclotrons K-120 of the University of Jyvaskula (Jyvaskula, Finland) and U-120 of the Institute of Nuclear Physics (Rez, Czech Republic). Registration and identification of the scattered reaction products was carried out by the ∆ Е-Е telescope of silicon semiconductor detectors. Analysis of elastic scattering was made within optical model. Both microscopic double folding potentials and phenomenological potentials were used for real part of complex nuclear potential. Imaginary part had the shape of phenomenological surface Woods-Saxon potential. The calculated theoretical cross sections are in good agreement with experimental data. The results obtained in this paper will be used to analyze the inelastic scattering of 3 Hе by 9 Bе nuclei and in the 3 Hе reaction on a 9 Bе target.